Resistance of modern spring barley cultivars to harmful organisms - A. G. Semenova; A. V. Anisimova; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции)
Background. Diseases and pests cause great damage to barley stands and harvests. Harvest losses from harmful organisms reach 25–30%.Materials and methods. During 2017–2020, 46 spring barley cultivars from the VIR collection, listed in the State Register for Selection Achievements, were studied for their resistance to fritfly, net and spot blotches, brown rust, and powdery mildew. The tests were carried out in the field with provocative colonization by fritfly and under natural infection pressure of leaf pathogens.Results and conclusions. In 2017, net blotch predominated over other diseases. In 2018, there was an epyphytotic outburst of spot blotch, and cultivars with weak development of this disease were identified. In 2019 and 2020, the incidence of brown rust and powdery mildew was significant, and the virulence of fritfly increased greatly in the same years. Field tests resulted in identification of 3 barley accessions resistant to fritfly: ‘Odon’ (k-31118, Buryatia), ‘Miar’ (k-31203, Orenburg Province), and ‘Omsky 99’ (k-31230, Omsk Province). Cv. ‘Posada’ (k-31245, Germany) was weakly affected by fritfly, brown rust and powdery mildew. Cultivars were selected for their low susceptibility to powdery mildew (up to 5%): ‘Chiraz’ (k-31131, Denmark), ‘Cheerio’ (k-31297, Denmark), and ‘Odyssey’ (k-31333, England), and brown rust: ‘Chiraz’ (k-31131, Denmark), ‘Eifel’ (k-31249, France), ‘Ursa’ (k-31339), and ‘Sunshine’ (k-31129, Germany). Such long-term assessment results can be used in breeding programs to develop cultivars with group or complex resistance to harmful organisms.